Leveraging sustainability of HEIs in Malaysia through lean and green strategies: A literature review and research agenda - Nawanir, Gusman; Lee, Khai Loon; Fatimah, Mahmud; Lim, Kong Teong (Science Publishing Corporation, 2018)
The journey towards sustainable development (SD) in Malaysia was started since the 1970s. Afterwards, a Malaysian New Economic Model (NEM) was formulated to pursue SD targeting high income, inclusivity and sustainability, which is in line with the 2030 SD agenda. Based on the goals of NEM, the Eleventh Malaysia Plan 2016-2020 (11MP) was developed. One of the 11MP coverage areas is education. In order to be sustainable, Malaysian higher-education institutions (HEIs) committed to corroborate this agenda by articulating an obligation to embrace the sustainability principles. However, within the Malaysian academic setting, it is still in its infancy, as most of the studies were constrained within the context of single university. In addition, to what extent the planning, strategies, and approaches for HEIs sustainability have been implemented tended to be neglected. Consequently, SD in HEIs is still far from being integrated into a holistic manner by policy makers. This paper extensively reviews the literature regarding the SD in the context of HEIs and provides some ideas for the future research leading towards the development of a comprehensive framework for sustainability development in Malaysian HEIs. Expectedly, this study could benefit policy makers, key players, and universities top management to progress towards sustainable university in an effective and efficient manner. It may strengthen the discourse on the implementation of SD initiatives within the Malaysian HEIs.